N,N-Dibenzyl-4-methylbenzenesulfonamide - Khan, I.U.; Ahmad, W.; Sharif, S.; Ali, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title compound, C(21)H(21)NO(2)S, comprises two molecules with similar conformations. The benzene rings of the nitrogen-bound benzyl groups lie to the same side of the molecule but are splayed in opposite directions precluding pi-pi interactions between them. In the crystal, each independent molecule self-associates via intermolecular C-H center dot center dot center dot O interactions, forming a supramolecular chain propagating along the b axis.